Assessment of microplastics contamination in riverine environments: Urban stretch of Cauvery and Kollidam rivers of southern India - S. Venkatramanan; K. Radhakrishnan; R. Muthuramalingam; K. Sivakumar; T. Kongeswaran; K. Prabakaran; R. Rameshkumar; V. Madavaraj (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Template complex synthesis of octadecan-1-amine with 2- benzoylpyridine and Cu2+: structural, anticancer, DPPH, SOD and FRAP studies - S. Vennila; K.S. Nagaraja; L. Lakshmi; V Radhakrishnan (Next Research, 2026)

Integrated biogasification and carbon capture pathways: a system-level review of technologies, storage options, and deployment challenges - Kamal Upreti; G. V. Radhakrishnan; Agnieszka Góra-Błaszczykowska; Saroj Date; Mamta Gautam; Rituraj Jain (Environment Systems and Decisions, 2026)

Genetic diversity assessment of near-threatened endemic catfish Clarias dussumieri in Western Ghats, India: implications for conservation - Divya Prema Radhakrishnan; Divya Merin Jose; C. P. Abhilash; V. S. Basheer; Uttam Kumar Sarkar (Hydrobiologia, 2026)

Phytomolecule-doped green synthesis of Ag@Fe bimetallic nanocomposites from Abutilon indicum leaf extract: Antimicrobial activity against Mycobacterium spp. and pathogenic bacteria and their cytotoxicity assessment in zebrafish embryos - Mary Shamya Arokiarajan; J. John Christopher; S. Ranjani; S.A. Wasim Akram; K.M. Ramkumar; S. Tirumala Santoshkumar; Noman Anwar; T. Rajaseker; M Radhakrishnan; V. Muzammil Ahmed; Murali Krishna Prasad; K. Kabiruddin Ahmed; et al. (Biocatalysis and Agricultural Biotechnology, 2025)

Comparison of clinical, radiological and outcome parameters in patients with progressive multifocal leukoencephalopathy (PML) with and without HIV infection: a cohort study - Farsana Mustafa; Anuj Ajayababu; Ajay Garg; Megha Brijwal; Divyani Garg; Manish Soneja; Aashish Choudhary; Lalit Dar; Shariq A. Shah; Venugopalan Y Vishnu; Animesh Ray; Neeraj Nischal; et al. (Journal of NeuroVirology, 2025)

Experimental validation of emamectin as predicted from the meta-analysis of in planta RNA-Seq data as a potential antifungal agent against Magnaporthe oryzae - Priya V. K; Riya Rachel Varghese; Jayachandran K; Radhakrishnan E. K (World Journal of Microbiology and Biotechnology, 2025)

Plant probiotic potential of rapid zinc-solubilizing Bacillus sp. VR in the presence of exogenously supplemented zinc oxide - P. Sruthi Parameswaran; V. K. Priya; K. Jayachandran; E. K. Radhakrishnan (Cereal Research Communications, 2025)

Atomic-level binding interaction analysis of Mycobacterium tuberculosis membrane protein Rv1085c with Toll-Like receptor 2 to investigate its role in immune response - Logesh Radhakrishnan; Irfan Navabshan; V. Lavanya; Shazia Jamal; Neesar Ahmed (In Silico Pharmacology, 2025)

Endophytic Xylaria sp. enhances tolerance in rice to bacterial leaf blight and promotes growth - K. Sushitha; A. Sajeena; N. V. Radhakrishnan; M. Joy; Jacob John; Swapna Alex; R. Beena (European Journal of Plant Pathology, 2025)

Novel o-Terphenyl Luminophores for Optoelectronic Devices: Synthesis, Photophysical, Electrochemical, and Thermal Analysis - Amarsinh R. Mainak; Pranjali S. Kewate; Vasanti B. Shabade; Vishnu V. Kutwade; Radhakrishnan M. Tigote; Netaji K. Desai; Sidram R. Pujari (Journal of Fluorescence, 2025)

Discovery of a potential phytochemical from Calotropis Procera to inhibit SARS-CoV-2 methyltransferase using molecular docking and MD simulation - Nayana Devang; Bhavya Banjan; Priya V．K．; Rajesh Raju; Jayachandran K．; Radhakrishnan E．K． (Next Research, 2025)

First report of stem canker disease caused by Neoscytalidium lignicola on dragon fruit in Kerala - Kovvuri Janakadatta Reddy; M. K. Dhanya; R. Ayisha; A. Sajeena; N. V. Radhakrishnan (Indian Phytopathology, 2025)

Bacillus licheniformis and commercial fungicides exhibit high potential against major pathogens inciting grain discolouration disease in rice, Oryza sativa L. - P. K. Amrith; M. Surendran; N. V. Radhakrishnan; Susha S. Thara; T. Anuradha; B. Ajay (Indian Phytopathology, 2025)

Whole genome sequencing based prediction of antimicrobial resistance evolution among the predominant bacterial pathogens of diabetic foot ulcer - Vipina Vinod T. N.; Manjusha Premnath; Jos V. Stanley; Nimmy Paul; Jyothis Mathew; E. K. Radhakrishnan (World Journal of Microbiology and Biotechnology, 2025)

Novel in-genome based analysis demonstrates the evolution of OmpK37, antimicrobial resistance gene from a potentially pathogenic pandrug resistant Klebsiella pneumoniae MS1 isolated from healthy broiler feces - Sreejith Sreekumaran; Priya V K; Manjusha Premnath; Prathiush P R; Anisha M N; Jyothis Mathew; Jayachandran K; Radhakrishnan E K (Science of The Total Environment, 2024)

Lyophilized rumen fluid as a ruminal fermentation modifier in high grain-fed acidotic goats - A. Ruba Nanthini; C. Valli; L. Radhakrishnan; D. Balasubramanyam; A. V. Mangalagowri (Tropical Animal Health and Production, 2024)

Energy efficiency and economics of small-scale fisheries (SSF) in India: A VIKOR based multicriteria decision-making model for sustainable fisheries management - Swathi Lekshmi Perumal Sundaram; Kalidoss Radhakrishnan; R. Narayanakumar; Vipin Kumar V. P; S. Surya; D. Divu; Nikita Gopal; Jose Kingsly; V.A. Leslie; Suresh Kumar Mojjada; Mayur Shivdas Tade; Aarsha Subramanian; et al. (Journal of Cleaner Production, 2024)

Effects of Zinc Oxide Nanoparticles Supplementation on Growth Performance, Meat Quality and Serum Biochemical Parameters in Broiler Chicks - V. Mozhiarasi; R. Karunakaran; P. Raja; L. Radhakrishnan (Biological Trace Element Research, 2024)

A Histone H2A Derived Antimicrobial Peptide from the Blue Swimmer Crab, Portunus pelagicus Linnaeus 1758: In silico Characterization and Phylogenetic Analysis - V. V. Anooja; P. P. Athira; Kesavan Dhanya; S. Neelima; M. V. Anju; K. Archana; S. Muhammed Musthafa; C. K. Radhakrishnan; Rosamma Philip (Thalassas: An International Journal of Marine Sciences, 2024)

Pixel Reduction of High-Resolution Image Using Principal Component Analysis - Ramachandran Radhakrishnan; Manimegalai Thirunavukkarasu; R. Thandaiah Prabu; G. Ramkumar; S. Saravanakumar; Anitha Gopalan; V. Rama Lahari; B. Anusha; Shaik Hasane Ahammad; Ahmed Nabih Zaki Rashed; Md. Amzad Hossain (Journal of the Indian Society of Remote Sensing, 2024)

Synthesis and characterization of gold nanoparticles using Brevibacterium casei (SOSIST-06) isolated from Southern Ocean water samples and their in vitro and in silico anti-WSSV activity - R. Namitha; B. Abirami; B.S. Anoop; D.V. Diya Dominic; Ahna Ameer; K. Manigundan; M. Radhakrishnan; P. Santhiya; Parli V. Bhaskar; K. Govindaraju; I.S. Bright Singh; G. Dharani (Aquaculture, 2024)

Mineral magnetic properties of ultisol profiles from tropical southern India - Mohan Reethu; Kizhur Sandeep; Joju G. Sebastian; Anish K. Warrier; Geetha H. Aravind; Abdul K. Rafaz; Jithin Jose; Radhakrishnan Akshay; Vadakkath V. Suhaiba (Geosciences Journal, 2023)

A critical review on pyrolysis method as sustainable conversion of waste plastics into fuels - K. Radhakrishnan; P. Senthil Kumar; Gayathri Rangasamy; L. Praveen Perumal; S. Sanaulla; S. Nilavendhan; V. Manivasagan; K. Saranya (Fuel, 2023)

C12orf57 pathogenic variants: a unique cause of developmental encephalopathy in a south Indian child - F. Alfiya; Manna Jose; Soumya V. Chandrasekharan; Soumya Sundaram; Madhusoodanan Urulangodi; Bejoy Thomas; Ashalatha Radhakrishnan; Moinak Banerjee; Ramshekhar N. Menon (Journal of Genetics, 2022)

Relative abundance of PGRs in the liquid endosperm of young nuts of Cocos nucifera L. parental cultivars and their reciprocal hybrids - V. V. Amritha; K. G. Ajith Kumar; Parvathy S. Nair; N. V. Radhakrishnan; K. Prathapan; B. N. Bessy Raj (Plant Physiology Reports, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Anti-inflammatory effect and mechanism of action of ellagic acid-3,3′,4-trimethoxy-4′- O -α-L-rhamnopyranoside isolated from Hopea parviflora in lipopolysaccharide-stimulated RAW 264.7 macrophages - B. Prabha; S. Sini; T. S. Priyadarshini; P. Sasikumar; Greeshma Gopalan; Jayesh P. Joseph; M. M. Jithin; V. V. Sivan; P. Jayamurthy; K. V. Radhakrishnan (Natural Product Research, 2021)

Protective effect of (+)–catechin against lipopolysaccharide-induced inflammatory response in RAW 264.7 cells through downregulation of NF-κB and p38 MAPK - M. A. Sunil; V. S. Sunitha; Prasanthkumar Santhakumaran; Mohind C. Mohan; Midhun Sebastian Jose; E. K. Radhakrishnan; Jyothis Mathew (Inflammopharmacology, 2021)

Promalabaricone B from Myristica fatua Houtt. seeds demonstrate antidiabetic potential by modulating glucose uptake via the upregulation of AMPK in L6 myotubes - B. Prabha; S. Sini; D. R. Sherin; S. Neethu; K. B. Rameshkumar; T. K. Manojkumar; P. Jayamurthy; K. V. Radhakrishnan (Natural Product Research, 2021)

A comparison of zooplankton assemblages in Nansi Lake and Hongze Lake, potential influences of the East Route of the South-to-North Water Transfer Project, China - Kandathil Radhakrishnan Divya; Shasha Zhao; Yushun Chen; Fei Cheng; Lei Zhang; Jiao Qin; Thundiparambil Sathrajith Arunjith; V. Bjorn Schmidt; Songguang Xie (Journal of Oceanology and Limnology, 2021)

Genotyping-by-sequencing based genetic mapping reveals large number of epistatic interactions for stem rot resistance in groundnut - Sneha M. Dodia; Binal Joshi; Sunil S. Gangurde; Polavakkalipalayam P. Thirumalaisamy; Gyan P. Mishra; Dayama Narandrakumar; Pooja Soni; Arulthambi L. Rathnakumar; Jentilal R. Dobaria; Chandramohan Sangh; Annapurna Chitikineni; Sumitra V. Chanda; et al. (Theoretical and Applied Genetics, 2019)

Improving oil quality by altering levels of fatty acids through marker-assisted selection of ahfad2 alleles in peanut (Arachis hypogaea L.) - Sandip K. Bera; Jignesh H. Kamdar; Swati V. Kasundra; Pitabas Dash; Anil K. Maurya; Mital D. Jasani; Ajay B. Chandrashekar; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; Manish K. Pandey; Pasupuleti Janila; et al. (Euphytica, 2018)

Culturable Endophytic Bacteria of Ginger Rhizome and their Remarkable Multi-trait Plant Growth-Promoting Features - Sabu Rohini; R. Aswani; M. Kannan; V. P. Sylas; E. K. Radhakrishnan (Current Microbiology, 2018)

Synthesis of substituted 2H-chromenes by a three-component reaction as potential antioxidants - Chitreddy V. Subbareddy; Radhakrishnan Subashini; Shanmugam Sumathi (Molecular Diversity, 2017)

Photochemical Degradation of Curcumin: a Mechanism for Aqueous Based Sensing of Fluoride - Roopa Venkataraj; C. P. Girijavallabhan; P. Radhakrishnan; V. P. N. Nampoori; M. Kailasnath (Journal of Fluorescence, 2017)

Spectral and Lensing Characteristics of Gel-Derived Strontium Tartrate Single Crystals Using Dual-Beam Thermal Lens Technique - I. Rejeena; V. Thomas; S. Mathew; B. Lillibai; V. P. N. Nampoori; P. Radhakrishnan (Journal of Fluorescence, 2016)

Effect of bilateral eyestalk ablation on ovarian development and moulting in early and late intermoult stages of female spiny lobster Panulirus homarus (Linnaeus, 1758) - Rachel Fernandez; E. V. Radhakrishnan (Invertebrate Reproduction & Development, 2016)

Spectral and Non Radiative Decay Studies of Lead Di Bromide Single Crystals by Mode Matched Thermal Lens Technique - I. Rejeena; B. Lillibai; V. Thomas; V. P. N. Nampoori; P. Radhakrishnan (Journal of Fluorescence, 2016)

Evaluating the stationarity assumption in statistically downscaled climate projections: is past performance an indicator of future results? - Keith W. Dixon; John R. Lanzante; Mary Jo Nath; Katharine Hayhoe; Anne Stoner; Aparna Radhakrishnan; V. Balaji; Carlos F. Gaitán (Climatic Change, 2016)

Population genetic structure of the shovel-nosed lobster Thenus unimaculatus (Decapoda, Scyllaridae) in Indian waters based on RAPD and mitochondrial gene sequences - N. S. Jeena; A. Gopalakrishnan; J. K. Kizhakudan; E. V. Radhakrishnan; Raj Kumar; P. K. Asokan (Hydrobiologia, 2016)

Solvent Dependency in the Quantum Efficiency of 4-[(4-Aminophenyl)-(4-imino-1-cyclohexa-2, 5- dienylidene) methyl] Aniline Hydrochloride - Bini Pathrose; V. P. N. Nampoori; P. Radhakrishnan; H. Sahira; A. Mujeeb (Journal of Fluorescence, 2015)

Marker-assisted introgression of a QTL region to improve rust resistance in three elite and popular varieties of peanut (Arachis hypogaea L.) - Rajeev K. Varshney; Manish K. Pandey; Pasupuleti Janila; Shyam N. Nigam; Harikishan Sudini; M. V. C. Gowda; Manda Sriswathi; T. Radhakrishnan; Surendra S. Manohar; Patne Nagesh (Theoretical and Applied Genetics, 2014)

Isolation of endophytic bacteria from embryogenic suspension culture of banana and assessment of their plant growth promoting properties - John C. Jimtha; P. V. Smitha; C. Anisha; Thomas Deepthi; George Meekha; E. K. Radhakrishnan; G. P. Gayatri; A. Remakanthan (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Measurement of Absolute Fluorescence Quantum Yield of Basic Fuchsin Solution Using a Dual-Beam Thermal Lens Technique - Bini Pathrose; V. P. N. Nampoori; P. Radhakrishnan; A. Mujeeb (Journal of Fluorescence, 2014)

UV-Visible Photoluminescence of TiO2 Nanoparticles Prepared by Hydrothermal Method - S. Mathew; Amit kumar Prasad; Thomas Benoy; P. P. Rakesh; Misha Hari; T. M Libish; P. Radhakrishnan; V. P. N. Nampoori; C. P. G. Vallabhan (Journal of Fluorescence, 2012)

Direct and Indirect Validation of Potential Fishing Zone Advisory off the Coast of Uttara Kannada, Karnataka - Sanjeev P. Deshpande; K. V. Radhakrishnan; U. Gopalakrishna Bhat (Journal of the Indian Society of Remote Sensing, 2011)

Impacts of hatchery release on genetic structure of rock carp Procypris rabaudi in the upper Yangtze River, China - Fei Cheng; Qingjiang Wu; Ming Liu; K. V. Radhakrishnan; Brian R. Murphy; Songguang Xie (Fisheries Science, 2011)

Invasion of the African sharp-tooth catfish Clarias gariepinus (Burchell, 1822) in South China - K. V. Radhakrishnan; Zhao Jun Lan; Jun Zhao; Ning Qing; Xio Lin Huang (Biological Invasions, 2011)

Shifting of Fluorescence Peak in CdS Nanoparticles by Excitation Wavelength Change - S. Mathew; Santhi Ani Joseph; P. Radhakrishnan; V. P. N. Nampoori; C. P. G. Vallabhan (Journal of Fluorescence, 2011)

Low-frequency internal waves and their influence on transmission loss variability - P. V. Hareesh Kumar; A. Raghunadha Rao; K. Anilkumar; M. Padmanabham; K. G. Radhakrishnan (Natural Hazards, 2011)

Response of west Indian coastal regions and Kavaratti lagoon to the November-2009 tropical cyclone Phyan - Antony Joseph; R. G. Prabhudesai; Prakash Mehra; V. Sanil Kumar; K. V. Radhakrishnan; Vijay Kumar; K. Ashok Kumar; Yogesh Agarwadekar; U. G. Bhat; Ryan Luis; Pradhan Rivankar; Blossom Viegas (Natural Hazards, 2011)

Identification of several small main-effect QTLs and a large number of epistatic QTLs for drought tolerance related traits in groundnut (Arachis hypogaea L.) - K. Ravi; V. Vadez; S. Isobe; R. R. Mir; Y. Guo; S. N. Nigam; M. V. C. Gowda; T. Radhakrishnan; D. J. Bertioli; S. J. Knapp; R. K. Varshney (Theoretical and Applied Genetics, 2011)

Otolith retrieval from faeces and reconstruction of prey-fish size for Great Cormorant (Phalacrocorax carbo) wintering at the East Dongting Lake National Nature Reserve, China - K. V. Radhakrishnan; Ming Liu; Wenping He; Brian R. Murphy; Songguang Xie (Environmental Biology of Fishes, 2010)

Comparative study of interspecific genetic divergence and phylogenic analysis of genus Jatropha by RAPD and AFLP - D. V. N. Sudheer Pamidiamarri; Nirali Pandya; Muppala P. Reddy; T. Radhakrishnan (Molecular Biology Reports, 2009)

Enhanced activity of introduced biocontrol agents in solarized soils and its implications on the integrated control of tomato damping-off caused by Pythium spp - J. Jayaraj; N. V. Radhakrishnan (Plant and Soil, 2008)

Characterization of a Pseudomonas fluorescens strain from tomato rhizosphere and its use for integrated management of tomato damping-off - Jayaraman Jayaraj; T. Parthasarathi; N. V. Radhakrishnan (BioControl, 2007)

Three-dimensional stress analysis for the mechanics of plantar ulcers in diabetic neuropathy - V. J. Thomas; K. M. Patil; S. Radhakrishnan (Medical & Biological Engineering & Computing, 2004)

Development of UV-induced Carbendazim-resistant mutants of Trichoderma harzianum for integrated control of damping-off disease of cotton caused by Rhizoctonia solani - J. Jayaraj; N. V. Radhakrishnan (Journal of Plant Diseases and Protection, 2003)

Real-time automatic extraction of lumen region and boundary from endoscopic images - S. Kumar; K. V. Asari; D. Radhakrishnan (Medical & Biological Engineering & Computing, 1999)

Technique of distortion correction in endoscopic images using a polynomial expansion - K. V. Asari; S. Kumar; D. Radhakrishnan (Medical & Biological Engineering & Computing, 1999)